Redirecting Love and Poetry: Friendship, Marriage, and the Tenzone on the Terrace of Gluttony - Basile Kelly, Deana (Quaderni d'Italianistica, 2025)
This article traces the series of friendships depicted in Purgatorio 22 to 23 as a composite model of a dynamic relationship in the process of spiritual re-orientation. Presenting the friendship of Virgil and Statius as a Classical model of a righteous relationship, the poet presents two particular relationships undergoing righteous purgatorial renewal: one between Dante and his friend Forese Donati, and the other between Forese and his wife Nella. Examining the dialogue between Forese and the pilgrim on the ledge of gluttony as a re-enactment of the youthful tenzone exchange of poems between the two friends, I propose a re-assessment of the critical understanding of the tenzone as a form that is condemned by the mature Dante. Instead, exposing elements of transformative reciprocity in the tenzone reveals a poetic form that is exploited as a model of purgatorial re-orientation. Alongside this salvaging of the tenzone form, I propose a related re-assessment of the marital relationship between Forese and Nella, thus challenging Dante’s apparent lack of interest in the theme of marriage. Tracing scriptural resonances of “thirsting” in the larger episode of the terrace of gluttony, I suggest that Dante offers a model of passionate, righteous marital relationship that comes into relief when considered against the backdrop of this longer meditation on righteous friendships.